Competitive Advantage of Banking Industry in the Digital Age: A Bibliometric Approach - Judijanto, Loso; Novitasari, Salwa Aulia; Arini, Rani Eka (Westscience Press, 2025)
The digital age has fundamentally transformed the competitive dynamics of the global banking industry, necessitating the integration of advanced technologies, customer-centric strategies, and agile business models. This study conducts a comprehensive bibliometric analysis to explore the evolution, intellectual structure, and thematic trends in scholarly literature on competitive advantage in the banking sector from 2000 to 2024. Drawing data from the Scopus database and utilizing VOSviewer for visualization, the study identifies key research clusters centered around digital banking, fintech, artificial intelligence, customer experience, and financial inclusion. The findings reveal a shift from early infrastructural concerns to more strategic and behavioral focuses, underscoring the growing importance of personalization, trust, and innovation in achieving sustainable competitiveness. Co-citation and country collaboration analyses highlight the interdisciplinary nature of the field and the global distribution of research efforts, with India, the United States, and the United Kingdom emerging as central contributors. This study offers valuable insights for academics, practitioners, and policymakers, while also identifying gaps for future exploration in areas such as ESG integration, digital leadership, and organizational transformation.